P62 Immunological analysis and clinical profile of Chronic Hepatitis B Virus (HBV) infection in the younger patient. (6th September 2011) - Kennedy, P T F; Sandalova, E; Jo, J; Gill, U S; Li, L; Ushiro-Lumb, I; Naik, S; Foster, G R; Bertoletti, A
Abstract : Introduction: Establishing disease phase in chronic HBV is a critical step in long-term disease management. This classification has even more significance at a younger age, where a proportion of eAg positive patients are labelled 'immune tolerant' and treatment is deferred. However, disease phase is diagnosed on clinical phenotype only with little insight into immunological activity. Aim: The aim of this study was to investigate the immunological profile in HBV infected children and young adults across different phases of disease and to compare the HBV-specific responses detected with those of older HBV infected patients. Method: 45 children and young adults (median age 19, range 12–30) were recruited and followed longitudinally for a minimum of 12 months. Clinical profile included ALT, HBV DNA, quantitative HBsAg and, where available, biopsy fibrosis stage and NI scores. This was compared with the immunological analysis for each subject comprising: global T cell cytokine profile (frequency of T cells producing IFNα, IL-2, IL-4, TNFα and the ILs; 17, 8, 21, 22 and MIP-1a after PMA stimulation), quantity of T cells (CD4 and CD8) expressing exhaustion markers (PD-1, Lag-3, CTTL-4) and the presence of functional HBV-specific T cells (PBMC stimulated with overlapping HBV peptides covering envelope, core and E proteins). Results: Frequency of T cells producing immunosuppressive or Th2 cytokines (IL-10, IL-4) and (IL-8, IL-21) is similar between age matched HBV infected and non-infected young adults, while T cells with pro-inflammatory cytokines (IFNα, TNFα, IL-17) were increased in the HBV infected group (p≤0.05). In addition, IL-22 producing cells were present in HBV infected young adults while almost absent in age matched uninfected controls. T cells expressing exhaustion markers were increased in HBV infected patients irrespective of age and correlated with ALT activity. Contrary to predictions HBV-specific T cells were detected with greater frequency in younger HBV-infected subjects when compared with those found in older infected patients (p≤0.05). The HBV-specific T cell response in younger patients show a classical Th1/Tc1 cytokine production profile and expands more vigorously than that seen in older HBV patients. Conclusion: HBV infection in young patients did not induce a generic immune tolerant T cell cytokine profile. On the contrary, disease activity in chronic HBV appears to be independent of age. Furthermore, the detection of HBV-specific T cells and the presence of significant liver damage on biopsy in a proportion of our young adult patients underlines the dangers of labelling these patients as 'immune tolerant'. Our findings highlight the dynamic nature of chronic HBV and stress the importance of more formal disease assessment in children and young adults with early therapeutic intervention where indicated.